Durable immunotherapeutic response in molecularly complex pulmonary adenosquamous carcinoma: case report and literature review - Zhu, Jun; Xun, Xin; Liu, Jiayun; Su, Bin; Li, Yi; Chen, Hong; Huang, Meijin (Frontiers in Immunology, 2025)
Pulmonary adenosquamous carcinoma (ASC) is a rare and aggressive subtype of non-small cell lung cancer (NSCLC) with poorly defined molecular characteristics and therapeutic strategies. We present a 63-year-old male patient with stage IVa (cT4N3M1b) lung ASC. Next-generation sequencing (NGS) revealed co-occurring mutations in KRAS G12C, BRAF (non-V600E), PIK3CA, and FLT1. Biomarker analysis showed: PD-L1 expression of 18.11% (Tumor Proportion Score, TPS), a tumor mutation burden (TMB) of 3.7 mutations per megabase (mut/Mb), and microsatellite instability (MSI) classified as low (MSI-L) with an instability rate of 35.29%. As first-line treatment, the patient received six cycles of tislelizumab (a PD-1 inhibitor) combined with chemotherapy, followed by tislelizumab maintenance therapy for two years. The patient maintained sustained complete response (CR) with progression-free survival (PFS) reaching 46.5 months, significantly exceeding the typical median PFS of 8-12 months in advanced NSCLC populations. To our knowledge, this presents the first reported case of advanced pulmonary ASC harboring co-occurring driver mutations that demonstrated a remarkable response to immune checkpoint inhibitor (ICI) therapy. Our case highlights the critical role of comprehensive molecular profiling and rational combination strategies in managing rare lung cancer subtypes, establishing a potential treatment paradigm for genomically similar cases.